Methodology for quality assurance of school premises maintenance program processes in the Tacna region. - Calderón Paniagua, Dennys Geovanni (2016)
Objective: To develop a methodology for the assuranceof the quality of the processes ofthe Program of Maintenance of School Premises in the Region of Tacna to increase its effectiveness. Methodology: lt was used an application design, because it is oriented to solve a problem, which ¡is the lack of a methodology for the development of the processes of the Program of Maintenanceof School Premises. Results: Procedures and format based on flow charts of the School Site Maintenance Program processes were designed, which allowed a better understanding ofthe users. Conclusion: A methodology was developed for the quality assurance of the School Site Maintenance Program, which improved the effectiveness of the maintenance of the educational infrastructure of the Tacna Region.